Exploration of Engine Parameters for Emission Reduction in Gasoline-Ethanol Fueled Engines - Wawan Purwanto; Hasan Maksum; Ahmad Arif; Muhammad Latifur Rochman; Sujito Sujito; Kathleen Ebora Padrigalan (Automotive Experiences, 2024)
The main objective of this study is to develop spark ignition engine parameters that allow complete combustion while reducing dependence on fossil fuels. To achieve this goal, optimization of compression ratio, gasoline-ethanol mixture, ignition timing, and spark plug type was used. In addition, this study used water injection that continuously injects water before the intake manifold. In this study, the Taguchi method with the L9 orthogonal array was applied. According to the experimental verification results, the best combination to reduce exhaust emission levels is to utilize gasoline-ethanol (E70), a compression ratio (CR) of 15.6:1, an ignition degree of +4Â°, and a platinum spark plug. Meanwhile, the presence of water injection at 1.45 ml/s helps reduce vehicle exhaust pollutants.